In search of the socially critical in health education: Exploring the views of health and physical education preservice teachers in Australia. Issue 2 (5th February 2018) - Wright, Jan; O'Flynn, Gabrielle; Welch, Rosie
Abstract : Purpose: Health education still tends to be dominated by an approach designed to achieve individual behaviour change through the provision of knowledge to avoid risk. In contrast, a critical inquiry approach educates children and young people to develop their capacity to engage critically with knowledge, through reasoning, problem solving and challenging taken for granted assumptions, including the socially critical approach which investigates the impact of social and economic inequalities on, for example, health status and cultural understandings. The purpose of this paper is to explore the conditions of possibility for a socially critical approach to health education in schools. It examines the ways in which preservice health and physical education (HPE) teachers talked about their experiences of health education during their school-based practicum. Design/methodology/approach: In total, 13 preservice HPE teachers who were about to graduate with a Bachelor of Health and Physical Education from a university in New South Wales, Australia were interviewed for the study. Five group interviews and one individual interview were conducted. The interviews were coded for themes and interpreted drawing on a biopedagogical theoretical framework as a way of understanding the salience of particular forms of knowledge in health education, how these are promoted and with what effects for how living healthily is understood. Findings: The HPETE students talked with some certainty about the purpose of health education as a means to improve the health of young people – a certainty afforded by a medico-scientific view of health imbued with individualised, risk discourses. This purpose was seen as being achieved through using pedagogies, particularly those involving technology, that produced learning activities that were "engaging" and "relevant" for young people. Largely absent from their talk was evidence that they valued or practiced a socially critical approach to health education. Practical implications: This paper has practical implications for designing health education teacher programmes that are responsive to expectations that contemporary school health education curricula employ a critical inquiry approach. Originality/value: This paper addresses an empirical gap in the literature on the conditions of possibility for a socially critical approach to health education. It is proposed that rather than challenging HPE preservice teachers' desires to improve the lives of young people, teacher educators need to work more explicitly within an educative approach that considers social contexts, health inequalities and the limitations of a behaviour change model.